Lymphoma Distribution Trends from Single Institute of Pakistan: Spectrum of 212 Cases - Kamran, Durr-e-Sameen; Salam, Hira; Bukhari, Uzma; Sharafat, Shaheen (International Journal of Pathology, 2018)
Abstract:Objective: Lymphoid neoplasms encompass an enormous group with diverse subtypes. The incidence iscontrastingly diminished in developing countries. Pakistan lacks a national cancer registry for exactcharacterization of statistics. The objective of this study was to draw histopathological spectrum of lymphomasubtypes diagnosed and characterized at Histopathology section of Dow University of Health Sciences, Karachi.Methods: Every lymphoma case diagnosed at Dow Diagnostic Reference and Research Lab and Dow Universityof Health Sciences Karachi during study period (January 2014 – December 2015) was included without exception.Pertinent clinicopathological information was entered in a proforma. Paraffin-embedded tissue blocked wereretrieved from histopathology archives and cross-examined. Data was analyzed using SPSS 16.0.Results: Out of 212 lymphoma cases, 79% were of Non-Hodgkin Lymphoma (NHL) and 21% were of HodgkinLymphoma (HL). Diffuse Large B-cell Lymphoma (DLBCL) was the prevalent subtype. Nodular Sclerosis (NS)dominated the HL class. Mean age at onset was significantly higher for NHL (p<0.01). Male to female ratio was1.7:1. Cervical lymph nodes are most frequently involved site for primary nodal lymphomas, whereas GIT ispredominantly involved by extra-nodal group.Conclusion: Lymphomas render a considerable measure of morbidity and mortality globally. Due topronounced heterogeneity in divergent subtypes, their prevalence also varies and hinders understanding ofetiologic factors. Epidemiologic studies are paramount for improving our understanding and subsequent deliveryof healthcare. We have described the spectrum of lymphoma as registered in one hospital in Pakistan. Morestudies from developing countries on broader scale are imperative for streamlining future research goals.